Development of Aluminum and Copper Alloys for Electric Automotive Engines—From the Research Work at the University of Dunaújváros - Judit Pázmán (Engineering Proceedings)
In the project work, CES EDUPACK material selection software and Arc melter 500 arc remelting equipment were used to select good-performance materials and produce a sample. First, aluminum alloys were considered due to their low weight; alloys Al7075, Al6082, and EN AW 6022 in different states were examined for maximum hardness and electrical conductivity, and then the Cu–Cr–Zr alloy was analyzed. The test results showed that for the EN AW 6082 alloy, the specimens heat-treated at 480 °C for 2 h + 175 °C for 2 h following the ECAP (equal channel angular pressing) A route or C route technique gave the best hardness–electrical conductivity pair. In the case of the EN AW 7075 alloy, the artificially aged sample after 4× ECAP forming showed the maximum values. In the case of EN AW 6022, which according to the Ashby chart may be the best alloy for the value pair sought, this alloy was fabricated, resulting in only as-cast samples being analyzed. Of the Cu alloys, the Cu–0.49–0.21Zr alloy after heat treatment at 450 °C for 1 h gives the most favorable hardness–conductivity.